PENERAPAN AKUNTANSI PENYUSUTAN ASET TETAP BERDASARKAN PERNYATAAN STANDAR AKUNTANSI PEMERINTAH NOMOR 07 PADA DINAS PEKERJAAN UMUM PROVINSI SUAWESI UTARA - Rumbaru, Sahril; Elim, Inggriani; Kalalo, Meyli Y. B. (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
Statement of Government Accounting Standards (PSAP) 07 is the accounting standard for property, plant and equipment including recognition, determination of carrying amount, accounting treatment of revaluation and impairment of carrying value of property and equipment. This study aims to determine the suitability of the application of accounting depreciation of fixed asset based on PSAP 07 at the Public Works Department of North Sulawesi Province. The data used is the report of depreciation in fiscal year 2016. The method used is descriptive analysis method. The results of the research indicate that the Public Works Agency in the application of fixed asset depreciation, the determination of depreciation value, the useful life of the asset, the use of depreciation method and the determination of the book value of the asset is in accordance with PSAP 07, however in the implementation of recording into reporting depreciation of fixed assets, has not implemented it independently but is done by the Regional Financial Management and Asset Board (BPKAD) of North Sulawesi Province somehow it is not in accordance with the assumption of entity independence in Government Regulation Number 71 of 2010 on Government Accounting Standards. It is expected that the Public Works Department of North Sulawesi Province may apply accounting for depreciation in accordance into applicable regulations.Keywords : PSAP 07, Depreciation of Fixed Asset, Implementation of Depreciation